2010
DOI: 10.1029/2009jb006824
|View full text |Cite
|
Sign up to set email alerts
|

Structural interpretation of the coseismic faults of the Wenchuan earthquake: Three‐dimensional modeling of the Longmen Shan fold‐and‐thrust belt

Abstract: [1] The 2008 M w 7.9 Wenchuan earthquake is a result of ongoing India-Tibet collision and reflects the growth of the Longmen Shan fold-and-thrust belt. In this paper, we construct a 3-D structural model of the geometry of the coseismic faults and related structures of the Wenchuan earthquake by integrating geological investigations, relocated aftershocks, and seismic reflection profiles. In the 3-D structural model, the differences between the southern and northern segments of the rupture are highlighted. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 72 publications
6
81
0
Order By: Relevance
“…Based on fault-related folding theories (Suppe, 1983;Shaw et al, 2005), we suggest that a shallowing of the dip of the Beichuan thrust to a detachment between ∼16-20 km is consistent with the earthquake data, the surface fault constraints, and the location and geometry of the synclinorium. While other solutions for the fault geometry at depth are likely permissible, we suggest that this interpretation is compatible with tomographic observations of a low-velocity zone at depths of 16-26 km beneath the range (Huang et al, 2009), as well as the fact that very few earthquakes have occurred beneath those depths (Li et al, 2010).…”
Section: Character Of the Wenchuan Rupturesupporting
confidence: 57%
See 2 more Smart Citations
“…Based on fault-related folding theories (Suppe, 1983;Shaw et al, 2005), we suggest that a shallowing of the dip of the Beichuan thrust to a detachment between ∼16-20 km is consistent with the earthquake data, the surface fault constraints, and the location and geometry of the synclinorium. While other solutions for the fault geometry at depth are likely permissible, we suggest that this interpretation is compatible with tomographic observations of a low-velocity zone at depths of 16-26 km beneath the range (Huang et al, 2009), as well as the fact that very few earthquakes have occurred beneath those depths (Li et al, 2010).…”
Section: Character Of the Wenchuan Rupturesupporting
confidence: 57%
“…10). In many cases, such as in the Zhongba thrust sheet, Cenozoic structures have clearly reactivated older Mesozoic fault systems (Burchfiel et al, 1995;Jia et al, 2006;Li et al, 2010). Exhumation rates imply that the present relief of the mountain belt has largely formed since the Miocene (Kirby et al, 2002).…”
Section: Tectonic Setting Of the Wenchuan Earthquake In The Longmen Shanmentioning
confidence: 99%
See 1 more Smart Citation
“…The GPS coseismic displacements mainly reflect the elastic deformation of the upper crust, and therefore, the observed eastward movement of the Bayan Har block, which accelerated overtime, might be affected by deep tectonic deformation. There are many tectonic models of the Longmen Shan fault zone (Hubbard and Shaw, 2009;Li et al, 2010;Yao et al, 2012), however, it is difficult to define how the deep tectonics affect crustal deformation clearly due to the current limitations in the accuracy and density of the GPS observations. In subsequent work, we will study the observed crustal deformation in combination with the deep tectonics.…”
Section: Discussionmentioning
confidence: 98%
“…Yutian earthquake is caused by a normal fault, which implied extension setting [21,22]. Wenchuan earthquake indicated the intense activation of Longmen Shan thrust-fold belt, which is a typical compressive tectonic environment [23][24][25]. Kunlun Shan earthquake in the north of the block and Yushu earthquake in the south of the block suggested the strike slip of Kunlun Shan fault and Yushu-Xianshuihe fault [26][27][28].…”
Section: Introductionmentioning
confidence: 99%